Bahan Ajar Kajian Puisi Berbasis Kearifan Lokal (Piil Pesenggiri) Dengan Dukungan Media Interaktif Prezi Presentation - Dewi Ratnaningsih; Nur Mei Ningsih (Edukasi Lingua Sastra, 2019)
The legal basis for the application of learning based on local wisdom in higher education in Indonesia is contained in Permenristekdikti Number 44 of 2015concerning the National Standards of Higher Education (SNPT). This is the basis of this research article. This study is entitled "Teaching Material Based on Local Wisdom (Piil Pesenggiri) with the Support of Interactive Learning Media Based on Prezi Presentation". The research objective is to design teaching materials based on local wisdom (Piil Pesenggiri) with the support of interactive learning media based on Prezi Presentation. Based on the results of the study it can beconcluded that: 1) by internalizing the values contained in the Pesenggiri Piil in Poetry Study teaching materials, students are able to get positive values on poetry; 2) by involving local wisdom in teaching materials, students are able to absorb the norms and values contained in the Pesenggiri Piil; 3) entering theIndustrial Revolution 4.0 era, teaching materials supported by interactive learning media based on Prezi Presentation are very relevant and more interesting.